P299 A novel ileocolonic Crohn's staging tool: the development and validation of an evidence-based, end-user informed radiological decision-aid. (25th January 2019) - Morar, P S; Wasmann, K A; Fareleira, A C T; Sahnan, K; Adegbola, S O; Mainta, E; Ilangovan, R; Arora, S; Sevdalis, N; Koysombat, K; Hart, A; Burling, D; et al.
Abstract: Background: Consensus guidelines emphasise the importance of multi-disciplinary team driven care for patients with complex Crohn's disease (CD). There are, however, no clear definitions of complex ileocolonic CD beyond the presence or absence of preoperative intra-abdominal sepsis. This study aims to develop a staging instrument (The St Mark's – Amsterdam tool) for complex ileocolonic CD based upon best evidence and end–user expert opinion and provide validation and reliability evidence for this tool. Methods: Items for the staging tool were developed using literature review and semi-structured interviews. Validity was tested using surgical outcome measures which were reviewed against intra-operative and histopathologically (IoH) assigned stages. Reliability was tested against IoH assigned stages using cross-sectional imaging, which were used to provide an objective pre-operative stage for patients who have undergone ileocolonic resection. Results: A 4 stage tool was constructed. The St Mark's – Amsterdam tool consists of 4 stages of escalating disease advancement mirroring radiological features identified from literature review and end user opinion. Validity testing with 324 patients demonstrated greater proportions of males ( p < 0.005), patients without preoperative biologics ( p < 0.05), patients with preoperative anaemia ( p < 0.001), leukocytosis ( p < 0.001), thrombocytosis ( p < 0.001), hypoalbuminaemia ( p = 0.001), CRP > 10 ( p < 0.001), emergent surgery ( p < 0.001), open surgery ( p < 0.001), concomitant sigmoidectomy ( p < 0.001), and pre-emptive stoma formation ( p < 0.001), with increasing IoH stage, respectively. Eighty-four patients had preoperative cross-sectional imaging prospectively staged. Further testing demonstrated greater proportions of preoperative anaemia ( p = 0.03), concomitant sigmoidectomy ( p = 0.01), and pre-emptive stoma formation ( p < 0.001), with increasing preoperative radiological stage. As an overall measure of morbidity, pre-emptive stoma formation and postoperative intra-abdominal septic complication were combined, demonstrating higher morbidity rates per increment IoH ( p < 0.001) and radiological ( p < 0.05) stage increase. Reliability was demonstrated, with 44(52%), 6(7%), 25(30%) and 9(11%) patients per increment radiological stage increase, and 26(39%), 14(21%), 20(30%), and 7(10%) per increment IoH stage increase, respectively ( R = 0.8; p < 0.001). Conclusions: This novel staging tool has been validated to show greater morbidity with increasing stage severity. It can reliably be used to preoperatively stage patients, estimate morbidity, and inform surgical decision-making through a tailored operative risk management approach. Further multi-centre prospective validation of this tool is required for both clinical and research purposes.